2020
DOI: 10.1111/anu.13199
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory growth of Sobaity ( Sparidentex hasta ) and yellowfin seabreams ( Acanthopagrus latus ) relative to feeding rate during nursery phase

Abstract: Sobaity (Sparidentex hasta) and yellowfin (Acanthopagrus latus) seabreams are commercially important carnivorous fish species in the Persian Gulf and Oman sea regions. These sparids are considered as potential candidates for developing marine aquaculture due to their high economic value, great adaptability to culture conditions and domestication and easy propagation in captivity (Mozanzadeh, Marammazi, Yaghoubi, Agh, Pagheh, et al., 2017). As a matter of fact, the commercial success in aquaculture operation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
(70 reference statements)
3
6
0
Order By: Relevance
“…It should be mentioned that RFI in S. hasta in the T3 group was lower than the other groups, mainly due to cannibalism. In agreement with the results of the present study hyperphagia demonstrated in S. hasta and A. latus fingerlings that experienced feed restriction for 30 days then refed at satiation level for another 30 days (Mozanzadeh et al, 2020). The hyperphagic behavior in response to FA and RF strategies also demonstrated in other Sparids such as S. aurata (Yilmaz and Eroldoğan, 2011), Dentex dentex (Pérez-Jiménez et al, 2012), A. schlegelii (Oh et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It should be mentioned that RFI in S. hasta in the T3 group was lower than the other groups, mainly due to cannibalism. In agreement with the results of the present study hyperphagia demonstrated in S. hasta and A. latus fingerlings that experienced feed restriction for 30 days then refed at satiation level for another 30 days (Mozanzadeh et al, 2020). The hyperphagic behavior in response to FA and RF strategies also demonstrated in other Sparids such as S. aurata (Yilmaz and Eroldoğan, 2011), Dentex dentex (Pérez-Jiménez et al, 2012), A. schlegelii (Oh et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, A. latus juveniles subjected to a short-term FA and RE periods two days of FA that followed by 8 days of RF for 80 days showed full CGR. In addition, Mozanzadeh et al (2020) reported that A. latus fingerlings subjected to 30 days of moderate feeding restriction (feeding rate at 6-8% of BWi) demonstrated full CGR following 30 days of RF at satiation level. But A. latus subjected to a severe feed restriction (feeding rate at 2-4% of BWi) for 30 days showed partial CGR (Mozanzadeh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in S . hasta , the CGR of fish during 6 weeks of satiation feeding was attributed to remarkable increase in SGR and improvement of FCR as previously reported by Mozanzadeh, Marammazi, Yaghoubi, Yavari, et al (2017), Mozanzadeh et al (2020). However, in A .…”
Section: Discussionsupporting
confidence: 77%